The effectiveness of an educational approach by teaching style for the team to learn some basic football skills for school students (ages 13-15 years) - Moussa, Mohamed; Mohsen , Raed; Sajit , Hussein Munati (International Journal of Psychosocial Rehabilitation, 2020)
This research is aiming to identify the effect of the educational program on the team’s teaching method on learning some basic football skills for students, as the researchers have used the experimental method by using the two equivalent groups style, pre and post measurement, as it suits the nature of the problem. The research community is determined for school students ages (13-15 years) for the academic season 2018-2019, which numbered (90) students. The curriculum has taken (12) educational units by four educational units for each skill, where each educational unit takes (90) minutes and by two educational units per week. One of the most important conclusions reached by the researchers is that the team’s teaching style is distinguished by quickly learning and acquiring sport skills better with lesser time.